Single-walled carbon nanotube membranes as non-reflective substrates for nanophotonic applications. (7th December 2020) - Zhigunov, Denis M; Shilkin, Daniil A; Kokareva, Natalia G; Bessonov, Vladimir O; Dyakov, Sergey A; Chermoshentsev, Dmitry A; Mkrtchyan, Aram A; Gladush, Yury G; Fedyanin, Andrey A; Nasibulin, Albert G
Abstract: We demonstrate that single-walled carbon nanotube (SWCNT) membranes can be successfully utilized as nanometer-thick substrates for enhanced visualization and facilitated study of individual nanoparticles. As model objects, we transfer optically resonant 200 nm silicon nanoparticles onto pristine and ethanol-densified SWCNT membranes by the femtosecond laser printing method. We image nanoparticles by scanning electron and bright-field optical microscopy, and characterize by linear and Raman scattering spectroscopy. The use of a pristine SWCNT membrane allows to achieve an order-of-magnitude enhancement of the optical contrast of the nanoparticle bright field image over the results shown in the case of the glass substrate use. The observed optical contrast enhancement is in agreement with the spectrophotometric measurements showing an extremely low specular reflectance of the pristine membrane (≤0.1%). Owing to the high transparency, negligibly small reflectance and thickness, SWCNT membranes offer a variety of perspective applications in nanophotonics, bioimaging and synchrotron radiation studies.